1338 Addressing psychosocial risk factor in the healthcare sector: the update of inail methodology with new assessment tools. (24th April 2018) - Ronchetti, M; Di Tecco, C; Balducci, C; Consiglio, C; Ghelli, M; Persechino, B; Iavicoli, S
Abstract : Introduction: Psychosocial Risk Factors was been a long-standing concerns of the healthcare sector. Several studies have shown that healthcare professionals are at an increased risk of work-related stress compared with other professionals. In Italy, according to the INSULA Survey findings, the healthcare sector was ranked first in terms of exposure to work-related stress risk. Therefore, specific approaches are needed to implement the assessment and management of psychosocial risk factors in this area. Methods: Starting from an existing methodology for the assessment and management of work related stress risk, that include a checklist (consisting of organisational indicators and work content and context factor) and a validated questionnaire (for the analysis of employees' perceptions related to seven organisational risk factors), we have identified specific topics for the health sector. Specifically, a detailed literature review has been carried out, followed by two focus groups with OSH professionals and experts of health sector, in order to identify what specific topics should be included. Subsequently, new tools were tested, involving 4 hospitals (more than 3000 workers). Results: Regarding the checklist, we have added: seven organisational indicators (eg. patients aggressions, precarious workers, ward mortality ratio) and seven work content and context factors (eg. shift work, organisational changes, procedures for managing conflicts). Among the additional scales of the questionnaire, those that reported better correlations with the pre-existing ones are: work-family conflict, emotional burden, poor team integration, and defensive attitude. Additionally, four outcome variables were added: work satisfaction, turnover Intentions, emotional exhaustion and relational burnout. Discussion: Within the framework of a research project funded by the Italian Ministry of Health, the Inail methodology has been integrated with new tools in order to provide a customised path for the healthcare sector. This proposal will be made available through an online platform for data collection and analysis.